Spirituality and reductionism: three replies - Paley, John (Nursing philosophy, 2010)
Several authors have commented on my reductionist account of spirituality in nursing, describing it variously as naïve, disrespectful, demeaning, paternalistic, arrogant, reifying, indicative of a closed mind, akin to positivism, a procrustean bed, a perpetuation of fraud, a matter of faith, an attempt to secure ideological power, and a perspective that puritanically forbids interesting philosophical topics. In responding to this list of felonies and misdemeanours, I try to justify my excesses by arguing that the critics have not really understood what reductionism involves; that rejecting reductionism is not the same as providing arguments against it; that the ethical dilemmas allegedly associated with reductionist views are endemic to health care; that ‘reifying’ is what believers in the spiritual realm do; and that the closed minds belong to those who dismiss reductionist science without having studied its achievements.